4-{2-[(Z)-(5-Methyl-2-furyl)methylideneamino]ethyl}benzenesulfonamide - Mahmood, Khalid (International Union of Crystallography, 2010)
In the title compound, C(14)H(16)N(2)O(3)S, the dihedral angle between the phenyl and 5-methylfuran groups is 54.89 (14)° and the C=N bond assumes a trans conformation. In the crystal, inversion dimers linked by pairs of N—H⋯O hydrogen bonds generate R (2) (2)(8) ring motifs. The dimers are interlinked by N—H⋯N hydrogen bonds, resulting in the formation of infinite chains extending along the b axis. The packing is consolidated by weak C—H⋯π interactions.